Best Practices of Solid Waste Management at Institute of Business Management, Karachi, Pakistan - Jamshaid Iqbal (Universitas Diponegoro, 2021)
Recently we conducted a study to evaluate the existing solid waste management practices at Institute of Business Management (IoBM), Karachi which shows that the institute possesses best management practices related to solid waste collection, transport, segregation, recycling/reuse, and final disposal. Adequate number of color-coded bins have been laid at appropriate locations throughout the university campus. Institute has enough staff for waste management including waste collection, transportation, and disposal. Results of our study indicate that about 2,033 kg of solid waste/month (24.5 tons/annum) is generated from the IoBM campus. Out of the total, about 67.8 % is the recyclable and reusable plastic, paper, and metal waste while, the remaining (about 32%) is mostly organic waste generated from various facilities of the university. Economic analysis indicates that about 252,012 Pak rupees annually are earned from selling the recyclable and reusable inorganic solid waste. Study also indicate that about 500 kg of good quality compost per month can be prepared from the organic waste including food and yard waste that can be used for existing horticultural activities at the university. Moving towards a sustainable integrated solid waste management system necessitates improved system of waste collection, segregation, reselling, and composting